Analysis of Bismuth (III) Iodide and Dendrimers in Drug Applications - Shahid Amin; M. A. Rehman; Amir Naseem; Jihad Younis; Syed Sheraz Asghar (Journal of Chemistry)
Dendrimers are spherical three-dimensional molecules with a repetitively branching core. They are normally symmetric around the core. Bismuth (III) iodide has the formula BiI3 and is an inorganic chemical. The reaction between bismuth and iodine produces this gray-black solid, which was of great interest in qualitative inorganic analysis. Mathematical chemistry is an area of mathematics that employs mathematical methods to tackle chemical-related problems. One of these tools is a graphical representation of chemical molecules, known as the molecular graph of a chemical substance. A topological index (TI) is a mathematical function that assigns a numerical value to a (molecular) graph and predicts many physical, chemical, biological, thermodynamical, and structural features of that network. In this work, we will calculate a new topological index, namely, Sombor index, multiplicative Sombor index, and its reduced version for bismuth (III) iodide and dendrimers. We also plot our computed results of Sombor index, multiplicative Sombor index, and reduced Sombor index to examine how they were affected by the parameters involved.